Electrophoretic deposition of YSZ layers on pyrolytic graphite and a porous anode substrate based on NiO-YSZ - Artem V. Solovev; Georgy N. Starostin; Inna A. Zvonareva; Stanislav S. Tulenin; Vyacheslav F. Markov (Chimica Techno Acta)
Solid oxide fuel cells are promising hydrogen energy devices. The goal of this research was to create ceramic layers for SOFCs based on yttria-stabilized zirconia (YSZ) and to investigate their parameters. YSZ ceramic layers with a thickness of 5.14 μm on a porous NiO–YSZ substrate and 7 μm on pyrolytic graphite were obtained by electrophoretic deposition. X-ray diffraction and electron microscopy were used to determine the composition, structure, and morphological features of ceramic layers. The effects of the substrate's nature, the degree of dispersion of the initial YSZ powder, and the heat treatment conditions on the properties of the ceramic layer YSZ were considered.